GIS-based assessment of aggregates in Carinthia (Austria) - Bäk, Richard; Heinrich, Maria; Letouzé-Zezula, Gerhard (Geologija, 2003)
For the last thirty years the Geological Survey of Austria (GBA) has made assessments of surface-near mineral resources putting emphasis on regional aspects of land use, environment and economy. In collaboration with land use experts, GlS-tools have been developed to evaluate the sustainability of mineral deposits, taking into account possible conflicts during it’s exploitation. An example for the province of Upper Austria, representing the main target of the 1990’s, has been shown at 1998’s ICGESA (Letouzé et al., 1998). Recent studies have focused on the province of Carinthia, where a Geological Information System has been designed which includes: • A GIS-based geological map “Setting of gravels, sands and clays” for the whole province of Carinthia (1:50.000 ArcINFO® concept). • Assessment, input and evaluation of basic data from archives, boreholes, pits and literature in general, in order to advance knowledge about surface-near mineral resources. Linking digital geological maps to specific data bases allows for the evaluation of mineral resources quality and usability, thereby contributing to a modern planning instrument within the administration of Carinthia. Internet and intranet availability of such data should initiate strategic mineral planning and strengthen sustainable land use in general. Equivalent treating of solid rocks is ongoing task required to complete land-use relevant mineral resources’ assessment in Carinthia. European regionalization efforts and the common future of Austria and Slovenia within the European Union may support at least comparable structuring of geological data. This paper outlines such an example for Carinthia, one of Austria’s boarder provinces to Slovenia.